Healthcare needs and barriers to care among female partners of male suspects of child sexual abuse material offences in Sweden: a qualitative interview study - Adebahr, Roberth; Savard, Josephine; Åkerstedt, Ulrika; Byström, Markus; Sparre, Charlotte; Hadding, Cecilia; Görts Öberg, Katarina; Jokinen, Jussi (Frontiers in Psychiatry, 2025)
ObjectiveTo explore the impact on female partners of the discovery that their significant other is under investigation for Child Sexual Abuse Material (CSAM) offences, with a focus on the need for professional support.DesignSemi-structured interviews were conducted and analyzed using reflexive thematic analysis.ParticipantsEight women partnered with men under investigation for CSAM offences.SettingANOVA, a center for sexual medicine, andrology, and trans medicine at Karolinska University Hospital, Stockholm, Sweden.ResultsThe findings show severe negative mental health impacts on partners following a disclosure that their significant other had committed CSAM offences. Identified healthcare needs include (1) crisis support in connection with police raid; (2) medical evaluation including suicide risk assessment and follow-up visits; and (3) counseling to manage shame, guilt, self-blame, and ambivalence regarding the future of the relationship. Significant barriers that hinder affected women from seeking and receiving support from friends and family as well as accessing healthcare services were also identified.ConclusionFemale partners of CSAM offenders have healthcare needs that are currently inadequately met by the Swedish healthcare system. Healthcare professionals, both in primary care and sexual medicine clinics, may significantly contribute to improving treatment for this population. However, there is a need for improvement of healthcare practitioners’ knowledge of the experiences and needs of family members of sexual offenders.